2019
DOI: 10.1002/path.5282
|View full text |Cite
|
Sign up to set email alerts
|

PGC‐1α deficiency causes spontaneous kidney inflammation and increases the severity of nephrotoxic AKI

Abstract: PGC‐1α (peroxisome proliferator‐activated receptor gamma coactivator‐1α, PPARGC1A) regulates the expression of genes involved in energy homeostasis and mitochondrial biogenesis. Here we identify inactivation of the transcriptional regulator PGC‐1α as a landmark for experimental nephrotoxic acute kidney injury (AKI) and describe the in vivo consequences of PGC‐1α deficiency over inflammation and cell death in kidney injury. Kidney transcriptomic analyses of WT mice with folic acid‐induced AKI revealed 1398 up‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 45 publications
0
83
0
Order By: Relevance
“…It has been previously reported that the severity of sepsis-associated acute kidney injury (AKI) correlates with PGC-1α levels in the kidney, and accordingly, lack of PGC-1α causes persistent kidney injury following endotoxemia [128]. In fact under the basal condition, PGC-1α KO mice display spontaneous subclinical kidney injury characterized by tubulointerstitial inflammation and exhibit a higher mortality rate than their wild-type (WT) littermates after AKI induction [129]. In addition, the expression of PGC-1α diminishes in aging muscle and has been associated with systemic inflammation in mice [130].…”
Section: Pgc-1α Inflammation and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that the severity of sepsis-associated acute kidney injury (AKI) correlates with PGC-1α levels in the kidney, and accordingly, lack of PGC-1α causes persistent kidney injury following endotoxemia [128]. In fact under the basal condition, PGC-1α KO mice display spontaneous subclinical kidney injury characterized by tubulointerstitial inflammation and exhibit a higher mortality rate than their wild-type (WT) littermates after AKI induction [129]. In addition, the expression of PGC-1α diminishes in aging muscle and has been associated with systemic inflammation in mice [130].…”
Section: Pgc-1α Inflammation and Oxidative Stressmentioning
confidence: 99%
“…After LPS/TNFα injection, the overexpression of PGC-1α in skeletal muscle does not suppress proinflammatory cytokine expression but lowers M1 cytokine IL-12 levels and enhances the production of anti-inflammatory M2 cytokines [142]. In addition, PGC-1α KO mice exhibit increased M1 and decreased M2 responses in the kidney after AKI induction [129]. Although the molecular mechanisms regulating macrophages polarization are poorly understood, these cells have been reported to be metabolically reprogrammed during polarization [143].…”
Section: Pgc-1α Inflammation and Oxidative Stressmentioning
confidence: 99%
“…acetylation but may in fact be related to increase histone crotonylation include preservation of the expression of the antiaging and nephroprotective gene Klotho despite the presence of Klotho suppressors such as inflammatory cytokines and albuminuria, and similar results were observed with PGC1a expression (Chen et al, 2018;Fernandez-Fernandez et al, 2018;Fontecha-Barriuso et al, 2019). This hypothesis should be addressed through specifically designed experiments.…”
Section: Histone Crotonylation In Kidney Injurymentioning
confidence: 75%
“…The increased histone crotonylation in cells stimulated with TWEAK and in AKI kidneys was associated with decreased PGC1a and Sirt-3 expression and with increased CCL2 expression, a chemokine which contributes to kidney inflammation (Ruiz-Andres et al, 2016a). PGC1a and Sirt-3 have nephroprotective actions (Kong et al, 2010;Morigi et al, 2015;Fontecha-Barriuso et al, 2019). Besides, Sirt3 and PGC1a regulate each other.…”
Section: Histone Crotonylation In Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation